Diffuse idiopathic skeletal hyperostosis-induced dysphagia or DISHphagia - Ozgocmen, Salih (My University, 2005)
Dysphagia related to osteophyte compression in diffuse idiopathic skeletal hyperostosis (DISH] or Forestiers disease and in cervical spondylosis has been identified as a cause of dysphagia. We report an elderly man who had dysphagia due to DISH or namely DISHphagia. Clinical findings, barium esophagogram, and magnetic resonance imaging findings have been presented. Good response to medical treatment with liquid forms of NSAIDs and soft diet has been achieved. ©Asia Pacific League of Associations for Rheumatology.
Keywords: Diffuse idiopathic skeletal hyperostosis; DISHphagia; Dysphagia